Development of multilanguage voice control for smart home with IoT - A. H., Ruslan; A. Z., Jusoh; Ani Liza, Asnawi; Md Rizal, Othman; N. I., Abdul Razak (IOP Publishing, 2021)
Internet of Thing (IoT) is very common and demanding nowadays and home automation system is not left behind in this technology. Home automation is the concept of making any home "smart". In this modern life, Automation is not a new thing. This technology has been using many years and normally can be seen in big companies. This automation concept can benefit our daily lives through many ways. However, the smart home technology in the market right now only support a few languages, generally English. For people who English is not their native language, it becomes a barrier in utilizing voice recognition installed in the smart home. Therefore this project will develop a Multilanguage IoT Home Automation System that focused on people who does not speak English especially elderly people in Malaysia to perform their chores routine such as turn on or turn off light by using voice commands given in their preferred language. Other than voice commands, it could be controlled wirelessly by using apps developed in the Smartphone. This system is based on Raspberry Pi and will be designed to be an affordable and reliable home automation system yet, easy to setup and use. The research focus on the methods of integrating voice recognition technology in many languages in home automation systems. This research can have a strong and positive impact to the society especially on persons with physical disabilities and older persons whom English is not their native language.